2019
DOI: 10.1186/s40101-018-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the differences in mental states on the mirror system activities when observing hand actions

Abstract: BackgroundIt is known that the activities of the mirror system are related to imitation and understanding of the intention of an action. It has been reported that the activity of the mirror system is higher for observations for imitating and understanding the intention of an action than for simple observations. However, observations that facilitate the mirror system’s activities, if they are observations intending to imitate an action or observations for understanding the intention of an action, have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…A separate consideration is concern over whether HRV is a reflection of the autonomic state of the entire body or the regulation of the sinoatrial node alone (Hayano and Yuda, 2019 ). The use of HRV as a sole index of ANS activity is potentially problematic given that frequency domain analysis of HRV reportedly over-simplifies the non-linear interactions between the SNS and PNS (Billman, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A separate consideration is concern over whether HRV is a reflection of the autonomic state of the entire body or the regulation of the sinoatrial node alone (Hayano and Yuda, 2019 ). The use of HRV as a sole index of ANS activity is potentially problematic given that frequency domain analysis of HRV reportedly over-simplifies the non-linear interactions between the SNS and PNS (Billman, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence indicates that subjective hunger and food intake do not influence HRV or other neurophysiological responses to food in normal subjects (Nederkoorn et al, 2000 ). Third, the traditional interpretation of HRV parameter has been challenged with regard to an over-simplified framework of HRV in the past (Hayano & Yuda, 2019 ). For example, Reyes et al ( 2013 ) suggested that LF may be the proxy of the parasympathetic system, rather than the sympathetic system.…”
Section: Discussionmentioning
confidence: 99%
“…L'hypothèse d'une contribution des neurones miroirs à la compréhension est corroborée par plusieurs études suggérant que ces neurones jouent un rôle actif lors de l'observation de l'action [98][99][100][101][102]. Notamment, Cole et al [102] ont mis en évidence que l'activité cortico-spinale évoquée par TMS est plus importante lorsqu'un sujet observe des actions dans le but d'inférer l'intention de celles-ci.…”
Section: Simuler Pour Comprendre ?unclassified